Long-Term Balancing Selection and the Genetic Load Linked to the Self-Incompatibility Locus in Arabidopsis halleri and A. lyrata - Le Veve, Audrey; Burghgraeve, Nicolas; Genete, Mathieu; Lepers-Blassiau, Christelle; Takou, Margarita; De Meaux, Juliette; Mable, Barbara K; Durand, Eléonore; Vekemans, Xavier; Castric, Vincent (Molecular biology and evolution, 2023)
Balancing selection is a form of natural selection maintaining diversity at the sites it targets and at linked nucleotide sites. Due to selection favoring heterozygosity, it has the potential to facilitate the accumulation of a "sheltered" load of tightly linked recessive deleterious mutations. However, precisely evaluating the extent of these effects has remained challenging. Taking advantage of plant self-incompatibility as one of the best-understood examples of long-term balancing selection, we provide a highly resolved picture of the genomic extent of balancing selection on the sheltered genetic load. We used targeted genome resequencing to reveal polymorphism of the genomic region flanking the self-incompatibility locus in three sample sets in each of the two closely related plant species Arabidopsis halleri and Arabidopsis lyrata, and used 100 control regions from throughout the genome to factor out differences in demographic histories and/or sample structure. Nucleotide polymorphism increased strongly around the S-locus in all sample sets, but only over a limited genomic region, as it became indistinguishable from the genomic background beyond the first 25-30 kb. Genes in this chromosomal interval exhibited no excess of mutations at 0-fold degenerated sites relative to putatively neutral sites, hence revealing no detectable weakening of the efficacy of purifying selection even for these most tightly linked genes. Overall, our results are consistent with the predictions of a narrow genomic influence of linkage to the S-locus and clarify how natural selection in one genomic region affects the evolution of the adjacent genomic regions.
Keywords: selekce (genetika); sheltered genetic load; nukleotidy; genetická zátěž; linked selection; Selection, Genetic; deleterious mutations; Genetic Load; balancing selection; polymorfismus genetický; self-incompatibility; Polymorphism, Genetic; Arabidopsis; S-locus; Nucleotides